Impact of Climate Changes on Skipjack tuna (Katsuwonus pelamis) catch during May-July in the Makassar Strait. (April 2019) - Putri, A R S; Zainuddin, M
Abstract: Climate change is underway, with unexpected consequences for various fields including fisheries. Fish distribution pattern shifts are not random, but are influenced by oceanographic factors and climate variability. This study aimed to analyze the impact of changes in climate on Skipjack tuna ( Katsuwonus pelamis ) catch in Makassar Strait. Time series satellite data on Sea Surface Temperature (SST) and Chlorophyll-a (chl-a) concentration (MODIS-aqua) during May-July were obtained for the period from 2012 to 2016. Catch per Unit Effort (CPUE) data for Skipjack collected during May-July 2017 were used to analyze the impact of oceanographic changes on the skipjack tuna fishery. This study used the anomaly method to analyze unusual phenomena in these time series. A Generalized Additive Model (GAM) was used to analyze the effect of climatic changes on skipjack tuna catch using the R 3.1.3 software package. Spatial data were mapped using ArcGIS 10.5 software. The results indicate that climatic changes included a significant increase in SST (0.26 − 0.80°C) and chl-a concentration (0.0280 − 0.0937 mg m −3 ) during May-July over the period 2012 - 2016 in the southern Makassar Strait. These conditions were significantly associated with increasing skipjack tuna catch, particularly chl-a in southern part of Makassar Strait.